„At vos … Primus in Epirum Boreas agat!” The Consuls’ Sea-passage to Greece in Lucan’s „Civil War” (2.645-648) - Plago, Mariusz (Collectanea Philologica, 2025)
This article analyzes lines 2.645-648 of Lucan’s Civil War. These four lines contain Pompey’s command for the consuls to sail from Brundisium to Epirus, and from there to proceed to Greece and Macedonia, where they were to gather reinforcements. According to the historical sources available to us, the consuls crossed to Dyrrachium, transporting the majority of the army and possibly civilians staying in Pompey’s camp. However, the issue lies in the north wind, Boreas, mentioned in line 2.646, where we would expect a south wind. The first part of the article examines various proposed solutions to this issue, which aim to reconcile Lucan’s lines with historical accounts. The second part offers an alternative interpretation: the consuls’ destination is not Dyrrachium. Instead, the analysis suggests that Lucan’s narrative assigns the consuls a new mission and alters their route for poetic purposes. This change stems from Lucan’s intertextual engagement with Virgil’s Aeneid and enhances the metaphorical dimension of the narrative. It helps establish a stronger parallel between Pompey’s departure from Brundisium and Aeneas’s flight from Troy.